2023
DOI: 10.1097/bco.0000000000001247
|View full text |Cite
|
Sign up to set email alerts
|

Orthopaedic surgery residency program ranking and the current state of leadership: what are the characteristics of the leaders in the “Top-tier” programs?

Fernando A. Huyke-Hernández,
Stephen A. Doxey,
Lily J. Qian
et al.

Abstract: Background: Orthopaedic surgery residency program ranking and leadership can influence applicant and program decision-making. The study objective was to evaluate the relationship between program rankings and characteristics of their leadership. Methods: The Accreditation Council for Graduate Medical Education, Doximity, and program-specific websites were queried, identifying 193 programs and 426 leaders for analysis. Leadership positions evaluated inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Therefore, while our study did not find a significant difference between the proportion of women in program directorship of the top and bottom 50 of the programs we included, it is likely that there will be a significantly higher proportion of female program directors in the top 100 programs we included vs. the bottom 100. Furthermore, given the results of our study, the Julian et al five-year update, and the Huyke-Hernandez et al "top-tier" program analysis, future studies can hypothesize that the faculty of higher-ranked programs are more gender diverse, which could correlate with the higher proportion of female leaders [18] and residents (our present study) at higher-ranked programs.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Therefore, while our study did not find a significant difference between the proportion of women in program directorship of the top and bottom 50 of the programs we included, it is likely that there will be a significantly higher proportion of female program directors in the top 100 programs we included vs. the bottom 100. Furthermore, given the results of our study, the Julian et al five-year update, and the Huyke-Hernandez et al "top-tier" program analysis, future studies can hypothesize that the faculty of higher-ranked programs are more gender diverse, which could correlate with the higher proportion of female leaders [18] and residents (our present study) at higher-ranked programs.…”
Section: Discussionmentioning
confidence: 49%
“…We examined program directors from the top 100 programs based on reputation, while Elkadi et al assessed those from 200 orthopedic residency programs, suggesting increased female representation in program directorship at higher-ranked programs [17]. Indeed, a paper investigating the characteristics of leadership in "top-tier" orthopedic surgery residency programs supports this, as they found that higher-tier programs had a larger proportion of women leaders with statistical significance after examining 193 programs [18]. Therefore, while our study did not find a significant difference between the proportion of women in program directorship of the top and bottom 50 of the programs we included, it is likely that there will be a significantly higher proportion of female program directors in the top 100 programs we included vs. the bottom 100.…”
Section: Discussionmentioning
confidence: 86%
“…It was a cross-sectional extraction of data that cannot identify influence or causation among studied variables and outcomes. The present study employed the methodology of prior published works that incorporated Doximity in orthopaedics 24,25 . The current study relies upon the accuracy of various internet sources concerning leadership information, which may affect the results.…”
Section: Discussionmentioning
confidence: 99%